Enriching PhD Education through Professor Assistantships and Research Collaborations-Insights from Columbia Teachers College and Drawing Parallels with PhD Programs in Georgian Universities - Machitidze, Irma; Bakhtadze, Irina (European Scientific Journal, ESJ, 2025)
Postgraduate education has always been a vital component of academic development, delivering specific expertise and knowledge and advancing innovation throughout different sectors of science and industry. In the context of an ever-changing environment, universities seek to improve their postgraduate programs by embracing successful models from different parts of the world. This endeavor of improvement necessitates an integrating approach to forward-looking postgraduate studies, designed to equip learners with the knowledge and competencies needed to thrive not only in conventional scholarly careers but also in a broader spectrum of positions within non-academic circles. All earnest efforts should be made to nurture the competencies of doctoral students to become applicable for diverse fields, such as industry, public or private sectors, non-profit institutions, and business organizations, therefore facilitating graduates to find their way in a competitive labor market successfully. To this end, higher education institutions should adjust the curricula of their postgraduate programs to support doctoral students in utilizing the instructions and knowledge they receive in real-life situations beyond their academic surroundings. The paper explores the substantial role of university programs for professor assistantships and research collaborations, which aim to merge the academic and professional development of doctoral students, therefore leading to sustainable change in postgraduate education. Through qualitative methodology, the article examines the benefits of integrating practical teaching-learning experiences and collaborative research into doctoral studies. By examining the institutional policy papers and primary documents, including the curricula and policies for teaching/learning in postgraduate studies of Columbia Teachers College, NYU, and the latest changes to institutional regulations at International Black Sea University (IBSU), this paper demonstrates the benefits of professor assistantships and research collaborations for both PhD students and university staff. In addition, the paper aims to provide applicable recommendations for Georgian universities to focus on how these policies could be translated into practice to enhance the quality of postdoctoral education at the national level.